The Role of Stress Proteins in the Study of Allostatic Overload in Birds: Use and Applicability to Current Studies in Avian Ecology - Garth Herring; Dale E. Gawlik (The Scientific World Journal)
Stress proteins offer a measure of stress in birds at the cellular level that are an alternative to the glucocorticoids. Stress proteins are not biased by handling stress, the increase in stress proteins lasts longer than with other measures (e.g., corticosterone), and, therefore, they may be a more appropriate measure of long-term or chronic stress. However, caution should be practiced when using stress proteins because the level of stress needed to elicit a response may be higher than with corticosterone. Stress proteins have only recently been used to measure the response to competition, food limitation, growth, and parasitism in birds. In other taxa, the stress proteins have been used to measure genetic stress, temperature, toxins, UV radiation, and physical activity. Stress proteins increase the options available to avian ecologists for understanding how avian species respond to changes in the environment.